Human Geography in the Context of Spatial Perspective - Lasaiba, Mohammad Amin; Alnursa, Darling Surya (GEOFORUM, 2023)
Human geography is a branch of science that seeks to understand the complex interactions between humans and their physical environment. The spatial perspective is a central approach in human geography, emphasizing the importance of analyzing location, distribution, and spatial relationships in understanding geographical issues. This study explores various aspects of the spatial perspective in human geography, including its crucial role in understanding human geography, its historical development, and its theoretical implications. The introduction discusses the basic concepts of human geography and how the spatial perspective aids in analyzing human interactions with their physical environment. Furthermore, it explores the theoretical implications of the spatial perspective in human geography, including its impact on understanding human mobility, location and distribution analysis, and human vulnerability to natural disasters. The study also addresses the relevance of the spatial perspective in the context of future research directions in the field of human geography. Overall, this study highlights the essential role of the spatial perspective in understanding the interactions between humans and their physical environment within the framework of the human geography discipline.